Geopolitical Dynamics and the Potential of World War 3: Contemporart Analysis - Anita Zahra Choirun Nisa (Eduvest - Journal of Universal Studies, 2026)
The study examines the complex geopolitical dynamics that could lead to the potential outbreak of a Third World War. In the contemporary global landscape, characterized by shifts in power structures and emerging alliances, the study identifies key factors contributing to geopolitical tensions, including territorial disputes, resource scarcity, and the rise of nationalism. A qualitative approach, which involves a case study of current geopolitical conflicts, is used, focusing on important areas such as Eastern Europe, the South China Sea, the Middle East, and the recent tensions between the United States and Iran, as well as the Cambodia-Thailand border conflict. The analysis reveals that while diplomatic efforts and international organizations play an important role in conflict resolution, underlying competition and historical grievances remain significant threats to global stability. In addition, the study highlights how the rise of nationalism and regional conflicts, combined with climate change and resource competition, exacerbate these tensions. These findings underscore the importance of proactive diplomacy and collaborative strategies to reduce the risk of large-scale conflicts. This paper aims to contribute to the understanding of the contemporary geopolitical landscape and offer insights into potential pathways to prevent a Third World War, emphasizing the need for comprehensive international cooperation and conflict prevention mechanisms.